Regulation of gas marketing activities in Mexico - L. Brito, Dagobert; Rosellón, Juan (Estudios Económicos de El Colegio de México, 2003)
We study the implications of linking the Mexican natural gas price to the Houston price on the efficient marketing of gas in Mexico. We argue that Pemex should be permitted to enter into spot contracts or future contracts to sell gas. However, the price of gas should always be the net back price based on the Houston Ship Channel at the time of delivery. Pemex should not be permitted to discount the price of gas from the Houston netback price even in a nondiscriminatory fashion. This arrangement is transparent, it is easy to enforce and does not eliminate any legitimate market options for any of the parties involved. Pemex or consumers of gas can use the Houston market for hedging speculative transactions.